Immediate Effects of Intermittent Theta Burst Stimulation on Primary Motor Cortex in Stroke Patients: A Concurrent TMS-EEG Study - Zhongfei Bai; Jack Jiaqi Zhang; Kenneth N. K. Fong (IEEE, 2023)
The neurophysiological effect of intermittent theta burst stimulation (iTBS) has been examined with TMS-electromyography (EMG)-based outcomes in healthy people; however, its effects in intracortical excitability and inhibition are largely unknown in patients with stroke. Concurrent transcranial magnetic stimulation and electroencephalogram (TMS-EEG) recording can be used to investigate both intracortical excitatory and inhibitory circuits of the primary motor cortex (M1) instantly and the property of brain networks at once. This study was to investigate the immediate effects of iTBS on intracortical excitatory and inhibitory circuits, neural connectivity, and network properties in patients with chronic stroke, using TMS-EEG and TMS-EMG approaches. In this randomized, sham-controlled, crossover study, 20 patients with chronic stroke received two separate stimulation conditions: a single-session iTBS or sham stimulation applied to the ipsilesional M1, in two separate visits, with a washout period of five to seven days between the two visits. A battery of TMS-EMG and TMS-EEG measurements were taken before and immediately after stimulation during the visit. Compared with sham stimulation, iTBS was effective in enhancing the amplitude of ipsilesional MEPs (p = 0.015) and P30 of TMS-evoked potentials located at the ipsilesional M1 (p = 0.037). However, iTBS did not show superior effects on ipsilesional intracortical facilitation, cortical silent period, or short-interval intracortical inhibition. Regarding the effects on TMS-related oscillations, and neural connectivity, comparisons of iTBS and sham did not yield any significant differences. iTBS facilitates intracortical excitability in patients with chronic stroke, but it does not show modulatory effects in intracortical inhibition.